Determinants of Secondary School Teachers’ Purchase Intention Towards Ready-To-Eat Products in Dungun, Terengganu, Malaysia - Mohd Izwan Mohd Zaki; Nur Amira Syasya Mohammad Samauludin; Siti Fatima Muhamad; Zatul Iffah Mohd Fuza; Abdullah Muhamed Yusoff (Information Management and Business Review, 2025)
The increasing demand for ready-to-eat products has become a significant trend, particularly among busy professionals like secondary school teachers in Dungun, who often face time constraints due to their professional commitments. While consumer behavior and purchase intentions in Malaysia have been widely studied, limited research specifically explores secondary school teachers' purchase intentions toward ready-to-eat products. Therefore, the purpose of this study is to explore the factors, particularly the most significant ones, that impact secondary school teachers' purchase intentions for ready-to-eat products in Dungun. The study gathered 205 respondents by distributing a printed and online survey via WhatsApp to secondary school teachers in Dungun. Then, the data was analyzed using SmartPLS 4 to determine the frequency of demographic profiles, descriptive analyses, measurements, and structural models. This study reveals that the three independent variables- convenience, price and brand are significantly influenced by purchase intention, and brand is the most significant factor. Understanding the factors that influence school teachers to purchase their RTE items is crucial, as this knowledge will enable them to design high-quality RTE products.